Isopropyl Caffeate: A Caffeic Acid Derivative—Antioxidant Potential and Toxicity. (19th April 2018) - Lira, Andressa Brito; Montenegro, Camila de Albuquerque; de Oliveira, Kardilandia Mendes; de Oliveira Filho, Abrahão Alves; da Paz, Alexandre Rolim; de Araújo, Marianna Oliveira; de Sousa, Damião Pergentino; de Almeida, Cynthia Layse Ferreira; da Silva, Teresinha Gonçalves; Lima, Caliandra Maria Bezerra Luna; Diniz, Margareth de Fátima Formiga Melo; Pessôa, Hilzeth de Luna Freire
Abstract : Phenolic compounds, among them isopropyl caffeate, possess antioxidant potential, but not without toxicity and/or adverse effects. The present study aimed to evaluate the antioxidant activity and toxicity of isopropyl caffeate through in silico, in vitro and in vivo testing. The results showed that isopropyl caffeate presents no significant theoretical risk of toxicity, with likely moderate bioactivity: GPCR binding, ion channel modulation, nuclear receptor binding, and enzyme inhibition. Isopropyl caffeate induced hemolysis only at the concentrations of 500 and 1000  μ g/ml. We observed types A and O erythrocyte protection from osmotic stress, no oxidation of erythrocytes, and even sequestrator and antioxidant behavior. However, moderate toxicity, according to the classification of GHS, was demonstrated through depressant effects on the central nervous system, though there was no influence on water and food consumption or on weight gain, and it did present possible hepatoprotection. We conclude that the effects induced by isopropyl caffeate are due to its antioxidant activity, capable of preventing production of free radicals and oxidative stress, a promising molecule with pharmacological potential.